Cypripedium × microsaccos Kraenzl. (Orchidaceae: Epidendroideae): A natural hybrid of C. calceolus and C. shanxiense from Jilin, China - Wang, Qun; An, Jing; Wang, Yan; Zheng, Baoqiang; Zheng, Bao-Qiang (Phytotaxa, 2025)
This study documents a natural orchid hybrid, Cypripedium × microsaccos Kraenzl., recently discovered in Jilin Province, China, based on morphological characteristics and molecular biological evidence. Its parents are C. calceolus and C. shanxiense. Morphological analysis revealed that C. × microsaccos exhibits intermediate traits between its parents in terms of floral size, labellum color, and petal coloration. Molecular analysis using nuclear ribosomal internal transcribed spacer (ITS) and plastid ribulose-1,5-bisphosphate carboxylase/oxygenase (rbcL) gene markers further confirmed its hybrid origin. Through combined morphological and molecular evidence, this study not only verifies the taxonomic status of C. × microsaccos but also enriches the species diversity within the genus Cypripedium.